Trait variation across different life history stages of trees and its impact on net photosynthetic rate - Lu, Mingyuan; Song, Yuhan; Jin, Guangze (Frontiers in Plant Science, 2025)
IntroductionExploring the variation in plant functional traits from different perspectives not only helps to reveal how plants adapt to their environment but also reflects their ecological strategies. This study investigated the differences in trait variability across different life history stages and how these differences affect the net photosynthetic rate of trees.MethodsThe research measured photosynthetic traits, hydraulic traits, leaf morphological traits, and leaf stoichiometry at various life history stages, exploring the variation and coordination among functional traits at different stages.ResultsResults showed that (1) the sapwood specific hydraulic conductivity and leaf specific hydraulic conductivity exhibited the highest variability among all traits, while carbon and phosphorus content had the lowest variability. (2) Intraspecific trait variation accounted for a significant portion of the total variance, indicating extensive plasticity in ecological strategies and environmental adaptability among individuals of the same species. (3) Regarding different life history stages, small trees surpassed mature trees in several physiological indicators, including higher leaf specific hydraulic conductivity, sapwood specific hydraulic conductivity, whole-branch hydraulic conductivity, and contents of carbon, nitrogen, and phosphorus. (4) As trees grew, both net photosynthetic rate and hydraulic efficiency tended to decline, with a weakened synergy between them, suggesting that water and nutrient transport efficiency are key factors limiting tree growth.DiscussionIn summary, our findings emphasize the importance of water transport efficiency in photosynthesis and reveal the coordinated relationship between water transport and net photosynthetic efficiency across different life history stages of trees. These findings provide new insights into how trees adjust their functional traits to respond to environmental stress during their growth and have important implications for maintaining productivity and balancing biodiversity in forest ecosystems.